2019
DOI: 10.1016/j.heliyon.2019.e01897
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of hydatid cysts in patients undergoing liver and lung surgery in Tehran, Iran

Abstract: Hydatid cyst, caused by larval stages of Echinococcus granulosus, is a zoonotic parasitic disease with public health importance. The disease is cosmopolitan and endemic in Iran. We conducted a retrospective study of the records of Milad Hospital, Tehran, Iran to establish the proportion of lung and liver surgical procedures that were performed for removal of hydatid cyst and to investigate the demography of the population undergoing lung and liver hydatid cyst surgery in this hospital. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…However inconsistently Rooh-ul-Muqim KK et al [16] reported that females were commonest 62.79% and males were 37.20%. Others also observed female predominance [16,17]. In this study mean size of the cyst was 8.6 cm.…”
Section: Discussionsupporting
confidence: 58%
“…However inconsistently Rooh-ul-Muqim KK et al [16] reported that females were commonest 62.79% and males were 37.20%. Others also observed female predominance [16,17]. In this study mean size of the cyst was 8.6 cm.…”
Section: Discussionsupporting
confidence: 58%
“…This zoonotic disease has worldwide distribution and is endemic in many countries, including Iran [5]. Human CE is reported in all parts of Iran and is the basis for nearly 1% of all surgical procedures [6] and 25% of liver and lung surgeries [7]. The condition becomes symptomatic as the cyst grows, with highly variable clinical manifestations depending on location and size [8].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of patients included in our study was 40 ± 17 years, and the peak age group was 25-50 years. While some reports from other countries like Turkey, Iran and India showed relatively similar peak age, the incidence was higher in females than males [6,[13][14][15][16]. Rao et al, have postulated that women are involved more than men in farming and herding livestock in their country; therefore women have more risk to get the disease [16].…”
Section: Discussionmentioning
confidence: 99%